Experience of a Strategy Including CYP2C19 Preemptive Genotyping Followed by Therapeutic Drug Monitoring of Voriconazole in Patients Undergoing Allogenic Hematopoietic Stem Cell Transplantation - García-García, Irene; Dapía, Irene; Montserrat, Jaime; Martinez de Soto, Lucía; Bueno, David; Díaz, Lucía; Queiruga, Javier; Rodriguez Mariblanca, Amelia; Guerra-García, Pilar; Ramirez, Elena; Frías, Jesus; Pérez Martínez, Antonio; et al. (Frontiers in Pharmacology, 2021)
Many factors have been described to contribute to Voriconazole (VCZ) inter-patient variability in plasma concentrations, especially CYP2C19 genetic variability. In 2014, Hicks et al. presented data describing the correlation between VCZ plasma concentrations and CYP2C19 diplotypes in immunocompromised pediatric patients and utilized pharmacokinetic modeling to extrapolate a more suitable VCZ dose for each CYP2C19 diplotype. In 2017, in our Hospital, a clinical protocol was developed for individualization of VCZ in immunocompromised patients based on preemptive genotyping of CYP2C19 and dosing proposed by Hicks et al, CPIC clinical guidelines and routine therapeutic drug monitoring. We made a retrospective review of a cohort of 28 immunocompromised pediatric patients receiving VCZ according to our protocol. CYP2C19 gene molecular analysis was preemptively performed using PharmArray®. Plasma trough concentrations were measured by immunoassay analysis until target concentrations (1-5.5μg/ml) were reached. Sixteen patients (57.14%) achieved VCZ troughs target concentrations in the first measure after initial dose based on PGx. This figure is similar to estimations made by Hicks et al in their simulation (60%). Subdividing by phenotype, 90% of the CYP2C19 Normal Metabolizers/Intermediate Metabolizers and 100% of the Rapid Metabolizers (RM) and Ultrarrapid Metabolizers achieved target concentrations during treatment/prophylaxis in our cohort. We recommended modifications of the initial dose in 29% (n=8) of the patients. In RM ≥12 years old an increase of the initial dose resulted in 50% of these patients achieving target concentrations in the first measure after initial dose adjustment based only on PGx information. Our experience highlights the need to improve VCZ dose predictions in children and the potential of preemptive genotyping and TDM to this aim. We are conducting a multicentre, randomized clinical trial in patients with risk of aspergillosis in order to evaluate the effectiveness and efficiency of VCZ individualization: VORIGENIPHARM (EudraCT: 2019-000376-41).